2020
DOI: 10.1186/s13104-020-04959-w
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence and survival among hospitalized heart failure patients in a tertiary hospital in Tanzania: a prospective cohort study

Abstract: Objective: Management of heart failure is complex and multifaceted but adherence to medications remains the cornerstone of preventing avoidable readmissions, premature deaths, and unnecessary healthcare expenses. Despite of evidence-based efficacy on anti-failure drugs, poor adherence is pervasive and remains a significant barrier to improving clinical outcomes in heart failure population. Results:We enrolled 459 patients with diagnosis of heart failure admitted at a tertiary cardiovascular hospital in Dar es … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
6
31
2
Order By: Relevance
“…The present finding was also consistent with other studies conducted in Africa: Uganda, 56 , 57 Malawi 58 , Tanzania, 59 and South Africa. 60 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present finding was also consistent with other studies conducted in Africa: Uganda, 56 , 57 Malawi 58 , Tanzania, 59 and South Africa. 60 …”
Section: Discussionsupporting
confidence: 93%
“…The present finding was also consistent with other studies conducted in Africa: Uganda, 56,57 Malawi 58 , Tanzania, 59 and South Africa. 60 In this study, the commonest reasons reported for missing monthly benzathine prophylaxis injections was long distance from hospitals (56.9%), lack of money (38%), unaffordability (30.8%), and inconvenient work schedule (22.5%).…”
supporting
confidence: 93%
“…Our study considered hypertensive patients with no other complications while the study conducted by Pallangyo et al involved admitted patients with heart failure as a complication of uncontrolled hypertension. 21 The current study shows that; participants who were 64 and below years of age had higher level of treatment compliance compared to those with 65 and above. The results are comparable to those reported in the study conducted by Demoner et al in the city of Maringá and Choi et al in Korea which reported that young age group showed association with treatment compliance and older frustrated and , hence, stop taking drugs.…”
Section: Discussionmentioning
confidence: 52%
“…19,20 Our findings showed that compliance to antihypertensive was higher than that of the study conducted by Pallangyo et al in tertiary hospitals in Tanzania which reported that 25.3% were compliant to their hypertensive treatment. 21 Study conducted by Bovet et al in Temeke Dar es Salaam, reported low (34%) adherence of patients to antihypertensive treatment. 17 Similar to a study by Goweda and Shatla.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation